Whither Maine’s Population - Mageean, Deirdre; AvRuskin, Gillian; Sherwood, Richard (Maine Policy Review, 2000)
Demographic changes affect many aspects of a state’s economic and community well-being. Mageean, AvRuskin and Sherwood describe some of the potential impacts of Maine’s changing population. They note that the state’s population is aging; the percentage of Maine’s youth is declining faster than in other New England states; and that rates of growth remain relatively slow throughout most counties. The authors describe each of these trends, and discuss the implications for Maine’s labor force, education and health care systems. They also note that these trends will not be experienced similarly by all parts of the state. While some counties may be faced with school closures, others should begin planning now for school expansions. Similarly, in order to take care of the state’s growing elderly population, rural, poorer areas may need to adopt different strategies from urban, more prosperous areas. The authors caution readers to interpret their population predictions carefully. While predictions on births and deaths are reasonably stable, migration trends are notoriously sensitive to economic conditions. Hence, much depends on the economic health of Maine and the region in the years to come.
Keywords: Maine demographics; Maine population